ПЕ ДАГОГІ ЧНА ІНТЕР НАТУРА ЯК СКЛАДОВА ПР ОФЕ СІЙ НОЇ ПІ ДГОТОВКИ ФАХІ ВЦІ В В РЕ СПУБЛІЦІ КІПР - Voyevutko, N (Continuing Professional Education: Theory and Practice, 2019)
The author characterizes the peculiarities of teacher internship organization for future teachers of secondary technical and vocational education of the Republic of Cyprus. The article deals with the phases of teacher internship as a part of teacher’s training at the University of Cyprus